408 Racial Disparities in Long-Term Functional Outcome After Traumatic Brain Injury: An Update. (April 2023) - Bah, Momodou; Eden, Sonia Veronica; Chen, Alex; Simo, Leticia; Tummala, Shalini; Mahas, Rachel
Abstract : INTRODUCTION: Racial disparities in outcomes have been reported in various medical conditions and in patients with traumatic brain injury (TBI). Despite equal access to acute rehabilitation, blacks had significantly worse long-term functional outcomes after TBI than non-Hispanic whites (NHWs). Much effort has been placed on raising awareness, improving access to care, expanding research, and on closing racial disparity gaps in healthcare. METHODS: Patients followed and tracked in the Southeastern Michigan Traumatic Brain Injury System (SEMTBIS) database were inquired, including 95 non-Hispanic whites (NHWs) and 97 blacks. Severe TBI was defined as Abbreviated Injury Scale [AIS] score of 3–5. Patients from February 2010 to December 2019 were included. Long-term outcomes were measured by 1) the percentage of patients discharged to home, and 2) the Glasgow Outcome Scale-Extended (GOSE) score after 1 year. Student's T-test was used for numeric data analysis. Chi-square was used for categorical data comparison. RESULTS: There were no significant differences in initial TBI severity between non-Hispanic whites (NHWs) and blacks, measured by the admission Glasgow Coma Scale (GCS), the percentage of people who had midline shift >5 mm on brain CT, the number of days from injury to date out of posttraumatic amnesia, and of days from injury to following commands. More NHWs were discharged to low acuity facilities (80% versus 58.8%, P = 0.0014). A higher percentage of NHWs had an upper good recovery score, which is a GOSE score of 8 (23.1% versus 9.3%, P = 0.074) after 1-year follow-up. CONCLUSIONS: Despite efforts to mitigate racial disparities in medical outcomes after TBI, the blacks in Southeastern Michigan continue to score lower than NHWs on their long-term functional outcomes at one-year follow-up.